The Role of Folk Songs in Social Movements: A Case Study on the Separate Telangana State Formation in India - Krishnaiah, Krishnaiah (European Journal of Multidisciplinary Studies, 2018)
Folk songs are instrumental in people’s mobilization for social movements. In the cultural and social context, the folk art forms played a crucial role in raising the social consciousness towards various social movements in Telangana. Folk arts are instrumental in shaping the people’s consciousness. The role of folk songs is pivotal in social movements. The research paper depicts, how the folk songs had brought the collective identity and consciousness among the people of Telangana and had brought the separate statehood. From the time of Telangana armed struggle to Telangana State formation, the role of folk songs is enormous and played a definite significant role in the formation of Telangana... The folk song which had undergone metamorphosis into protest and revolutionary song had raised the voice against all major social exclusion and inclusion indicators like feudalism, social and economic exploitation, denial of power, resources exploitation, water crisis, underdevelopment, drought, poverty, alienation, suppression of cultural identity, social injustice, bonded labour, migration of labour, suicides, gender inequality, caste discrimination and for separate statehood in Telangana.
Keywords: The Role of Folk Songs in Social Movements: a Case Study on the Separate Telangana State Formation in India